Use the factor theorem to determine whether g(x) is a factor of f(x):
(ii) f(x)=2x3+4x+6; g(x)=x+1
Checking whether g(x) is a factor of f(x) or not.
Factor theorem: Let f(x) be a polynomial of degree greater than or equal to 1 and a is any real number, then
f(a)=0⇒(x-a) is a factor of f(x)
(x-a) is a factor of f(x) ⇒f(a)=0.
According to the factor theorem, g(x) is a factor of f(x), if f(-1)=0 [since, g(x)⇒ x+1=0 ⇒ x=-1]
Substitute -1 for xin the function f(x) and simplify.
f(-1)=2(-1)3+4(-1)+6⇒f(-1)=-2-4+6∴ f(-1)=0
As f(-1)=0, the given polynomial g(x) is a factor of f(x).
Hence, the polynomial g(x)=x+1 is a factor of f(x)=2x3+4x+6
Use the factor theorem to determine whether g(x) is a factor of p(x) in the given expression p(x) = 2x3 + x​​​​​​2 - 2x - 1,g(x) = x + 1